First principle study of the self‐switching characteristics of the guanine based single optical molecular switch using carbon nanotube electrodes. Issue 2 (22nd November 2018) - Dey, Debarati; Roy, Pradipta; De, Debashis
Abstract : The switching property of an optical single molecular switch based on a single DNA molecule guanine with a single walled carbon nanotube electrode has been investigated using density functional theory along with non‐equilibrium Green's function based first principle approach. The semi‐empirical model of this single bio‐molecular switch has been operated at an ultra‐high 25 THz frequency in mid‐UV range. This single bio‐molecule comprises switching activity upon UV photo‐excitation. The influence of the highest occupied molecular orbital and lowest unoccupied molecular orbital gap and the quantum ballistic transmission into the switching activity are discussed in detail in this study. It has been observed that the maximum ON–OFF ratio, i.e. 327 is obtained at +0.8 V bias voltage. Theoretical results show that current through the twisted form is sufficiently larger than the straightened form, which recommends that this structure has smart prospective application in the future generation switching nanotechnology.